Impact of stocking density during live transportation on meat quality of Nile tilapia ( Oreochromis niloticus ) and their changes during storage - Jaksuma Pongsetkul; Soottawat Benjakul; Sirima Takeungwongtrakul; Samart Sai‐Ut (Journal of Food Processing and Preservation, 2022)
Quality of Nile tilapia meat (Oreochromis niloticus) transported at the densities of 60, 180, 300, and 420 kg/m3 (D60, D180, D300, and D420) for 4–5 h, and their changes during frozen storage were evaluated and compared with control (immediately euthanized after catching). The result found that D60 and D180 had no significant difference in stress indicator’s levels including cortisol, glucose, and lactate, compared with control (p > .05), while D300 and D420 exhibited higher levels of those stress indicators than others, indicating the occurring of fish stress in the two latters. Among all samples, D300 and D420 exhibited a faster rate of postmortem changes as indicated by higher trichloroacetic acid (TCA)-soluble peptides, lipid oxidation products, and faster developments of ATP derivatives than others. D300 and D420 also had lower water-holding capacity (WHC) and higher cooking loss, compared with D60, D180, and control (p ≤ .05). Moreover, a faster rate of quality changes during frozen storage was obtained in these two samples. This brings to the significantly lower sensory acceptability at all period tests (p ≤ .05). Practical applications Pre-slaughter stress is an important issue in the fish industry, as it directly influences the welfare and meat quality of animals. Improper fish densities during live fish transportation are one factor that can cause pre-slaughter stress of fish and result in destroying fish meat quality. From this study, the result clearly indicated that transportation densities of Nile tilapia more than 300 kg/m3 were significantly able to suppress the prime quality of fish meat and accelerate quality changes during storage at −20°C.
Keywords: Meat and Animal Product Quality; Aquaculture Nutrition and Growth; Animal Nutrition and Physiology